Natural Polymeric Hydrogels Encapsulating Small Molecules for Diabetic Wound Healing - Elena Iulia Oprita; Andreea Iosageanu; Oana Craciunescu (Gels, 2023)
Diabetes is a condition correlated with a high number of diagnosed chronic wounds as a result of a complex pathophysiological mechanism. Diabetic chronic wounds are characterized by disorganized and longer stages, compared to normal wound healing. Natural polymer hydrogels can act as good wound dressings due to their versatile physicochemical properties, represented mainly by high water content and good biocompatibility. Natural bioactive hydrogels are polymers loaded with bioactive compounds providing antibacterial and antioxidant properties, modulation of inflammation and adherence to wounded tissue, compared to traditional dressings, which enables promising future applications for diabetic wound healing. Natural bioactive compounds, such as polyphenols, polysaccharides and proteins have great advantages in promoting chronic wound healing in diabetes due to their antioxidant, anti-inflammatory, antimicrobial, anti-allergic and wound healing properties. The present paper aims to review the wound healing mechanisms underlining the main issues of chronic wounds and those specifically occurring in diabetes. Also, the review highlights the recent state of the art related to the effect of hydrogels enriched with natural bioactive compounds developed as biocompatible functional materials for improving diabetic-related chronic wound healing and providing novel therapeutic strategies that could prevent limb amputation and increase the quality of life in diabetic patients.